Formation of Ciprofloxacin-Isonicotinic Acid Cocrystal Using Mechanochemical Synthesis Routes-An Investigation into Critical Process Parameters - Maryam Karimi-Jafari; Ahmad Ziaee; Emmet O'Reilly; Denise Croker; Gavin Walker (MDPI AG, 2022)
The mechanochemical synthesis of cocrystals has been introduced as a promising approach of formulating poorly water-soluble active pharmaceutical ingredients (APIs). In this study, hot-melt extrusion (HME) as a continuous process and grinding and ball milling as batch processes were employed to explore the feasibility of cocrystallization. Ciprofloxacin (CIP) and isonicotinic acid (INCA) were selected as the model API and coformer. CIP-INCA cocrystal was produced in all techniques. It was revealed that higher cocrystal content could be achieved at longer durations of grinding and ball milling. However, milling for more than 10 min led to increased co-amorphous content instead of cocrystal. A design of experiment (DoE) approach was used for deciphering the complex correlation of screw configuration, screw speed, and temperature as HME process parameters and their respective effect on final relative cocrystal yield. Statistical analysis showed that screw configuration, temperature, and their interaction were the most critical factors affecting cocrystallization. Interestingly, screw speed had minimal impact on the relative cocrystallization yield. Cocrystallization led to increased dissolution rate of CIP in phosphate buffer up to 2.5-fold. Overall, this study shed a light on the potential of mechanochemical synthesis techniques with special focus on HME as a continuous process for producing cocrystals.